The sustainable livelihoods index: A tool to assess the ability and preparedness of the rural poor in receiving entrepreneurial project - Kamaruddin, Roslina; Samsudin, Shamzaeffa (Pak Publishing Group, 2014)
This paper describes the Sustainable Livelihoods Index (SLI) as a useful tool in assessing the livelihood elements of the rural poor households. Income data alone may not fully reflect the suitability of the hardcore poor in receiving government assistance in the form of entrepreneurial projects.In this case rendered projects do not take into account the ability and preparedness of the poor in receiving the projects. The main objective of this study is to measure comprehensively all the livelihood elements of the rural poor households through developing a Sustainable Livelihood Index (SLI). This index was based on Sustainable Livelihood Approach (SLA) framework.A total of 22 livelihood assets and outcomes indicators were identified from the data set and broadly grouped into five groups of assets namely human, physical, natural, social, financial assets and 2 groups of livelihoods outcomes which are food security and health status. Then, an aggregate SLI for each household was constructed by averaging all the seven groups of livelihood assets and outcomes indices with an equal weight. Overall, about 73% of considered households were attained an SLI below than 0.5, with a mean of 0.47. With regard to household income that has been used as a poverty measurement, the study found that the Sustainable Livelihood Index (SLI) was moved in tandem with the total of household income. There are 90.91% of the households in hardcore poor group were obtained SLI below 0.5 indicating that households with a low income will also have a low SLI.Although income and SLI were moved in the same direction, this paper suggests the use of SLI as a more analytically rigorous tool to assess the ability and preparedness of the rural poor than the regular use of household income level alone. Besides it may help the local authorities to broaden their scope in a manageable way as to ensure the sustainability of a given project.